Pengaruh Teman Sebaya dan Sosialisasi Keuangan Keluarga Terhadap Literasi Keuangan Siswa SMA IT Nur Hidayah - Adila, Faizah Nurul; Indriayu, Mintasih; Wardani, Dewi Kusuma (Universitas Negeri Surabaya, 2024)
Data shows that teenagers' financial literacy levels are low. Low financial literacy increases the risk of teenagers being affected by financial risks. Financial socialization is one of the factors that encourages financial literacy. Socialization is carried out by peers and parents. In order to increase the level of financial literacy, it is necessary to know the influence of peers and family financial socialization on financial literacy. This research is quantitative with a population of class XI Nur Hidayah Integrated Islamic Highschool students. The Sampling was carried out using proportional random sampling technique. The number of samples obtained was 172 respondents. Data collection uses questionnaires and data analysis uses multiple linear regression analysis. The research results show that there is a significant positive influence, partially or simultaneously, by peers and family financial socialization on the financial literacy of IT Nur Hidayah High School students.